A study on the awareness and the acceptance of Islamic pawnshops / Noor Khamisah Abdul Latif, Mohd Jamili Abdul Rahim and Mohd Fazli Mohd Sam - Abdul Latif, Noor Khamisah; Abdul Rahim, Mohd Jamili; Mohd Sam, Mohd Fazli (Faculty of Business and Management, 2005)
In this research, we believed the product called Ar-Rahnu able to be marketed in every country and based on our preliminary observation the demand of the pawnshop service cannot be denied. Bank Pertanian Malaysia, one of the services offered in pawn-broking is known as Ar-Rahnu scheme or Islamic pawnshop is special scheme created and existed in Islamic law in order to help customers to get cash immediately by putting valuable materials such as gold as collateral. The significant of the research is to expose readers and the future researchers the feasibility of Islamic pawnshop and e-commerce implementation. Muslim and Non-Muslim will get the advantage of pawn-broking and will appreciate the system and grab the opportunities that exist. Conventional pawnshop had been existed in our country long time ago and still many people are using this system. Problems that we are concerned about are the customer's perception on the pawnshop services; weakness in the Bank Pertanian Islamic pawnshop promotion; the different between conventional and Islamic pawnshop concept; customer's opinion on the usage of SMS or e-commerce as marketing tools; and occasionally when customers do really need pawnshop services. To open the mindset of the users that using the conventional method, we try to get close and understand the perception and behavior of customers when using pawn-broking. By doing this project, we hope that more Islamic pawnshop will be established in the market. Recently only few local banks are doing this service and through this research we hope those problems indicated earlier can be solved. We also hope local pawnshop practitioner will be able to implement certain approach we suggested in this thesis.